High intensive light channel formation in the post-filamentation region of ultrashort laser pulses in air. (23rd August 2016) - Geints, Yu E; Ionin, A A; Mokrousova, D V; Seleznev, L V; Sinitsyn, D V; Sunchugasheva, E S; Zemlyanov, A A
Abstract: An experimental and theoretical study of the post-filamentation stage of focused high-power Ti:Sa-laser pulses in air is presented. For the first time to our knowledge, the angular and spatial characteristics of specific spatially localized light structures, the ionization-free post-filament channels (PFCs), formed inside the laser beam in the post-filamentation region are systematically quantified under different external focusing and energy of initial pulse. We show that PFC angular divergence tends to decrease with the increase of the laser pulse energy and beam focal distance. These findings are discussed in the framework of the Bessel–Gauss-like beam formation in a course of pulse filamentation stage.